(untitled) (Journal of Pedagogical Inventions and Practices, 2025)
This article discusses the role of science in higher education. Integrated lessons provide the student with a broad and vivid understanding of the environment in which he is studying, the existence of the material and immaterial world. In an integrated lesson, the main emphasis is not on mastering knowledge about the interrelationships of phenomena and objects, but on the development of figurative thinking